The Influence of Empowerment on the Motivation of Portuguese Employees—A Study Based on a Structural Equation Model - Marlene Sousa; Eulália Santos; Tânia Santos; Márcio Oliveira (Administrative Sciences, 2023)
Over the last few years, in a continuous and growing way, the motivation of employees has been studied and it is currently agreed that it is an important work factor that significantly influences productivity and individual performance in an organisational context. As an influential factor for this motivation, we can find psychological empowerment in the sense that it gives employees freedom and confidence. This study aimed to understand the role of psychological empowerment in employee motivation. Empowerment can be translated, in a business context, into the training and valorisation of collaborators with a sense of their commitment to better the individual and, consequently, global performance of the organisation. In this research, empowerment was considered a motivational factor in achieving organisational objectives. The methodology used was of a quantitative nature based on a questionnaire survey that aimed to analyse psychological empowerment and the motivation of 620 individuals working in Portuguese organisations in the industry and services sectors. The results obtained, which were based on a structural equation model, show that psychological empowerment at work positively influenced employee motivation, with the meaning and self-determination dimensions contributing the most to motivation. The results obtained in the study have the potential to benefit both employees and organisations, contributing to a more productive and healthy working environment.